Investigation of the changes in low molecular weight organic acids and other physiological parameters by nitric oxide application in two wheat cultivars exposed to boron stress. (28th May 2017) - Tepe, Hafize Dilek; Aydemir, Tülin
ABSTRACT: Boron (B) is one of the essential nutrients for the growth of plants, but its high concentrations are toxic for plants. Thus, B toxicity is a big challenge in crop cultivation. Nitric oxide (NO) is a small signaling molecule that has cytoprotective roles in plants. We investigated whether exogenous sodium nitroprusside (SNP), which is a NO donor, may succeed to alleviate B-induced toxicity in wheat cultivars. Seedlings were grown for 10 days in a growth chamber at 25°C with 16 hr light–8 hr dark photo cycle. After high B application, the effects of SNP on growth parameters; electrolyte leakage (EL); changes in reactive oxygen species [contents of hydrogen peroxide (H2 O2 ), malondialdehyde (MDA), and proline]; the activities of antioxidant enzymes [glutathione peroxidase (GSHPx), glutathione reductase (GR), and glutathione S-transferase (GST)] and nitrate reductase (NR); and low molecular weight organic acid (LMWOAs) contents and also chlorophyll and total carotenoid contents were investigated in both shoots and roots of two different wheat cultivars. All experiments were carried out in triplicate. 0.2 mM SNP application ameliorated the chlorophyll and total carotenoid contents, and growth parameters such as shoot length, root length, and fresh weight in both wheat cultivars exposed to B stress. SNP reduced the B-induced lipid peroxidation, EL, and proline and H2 O2 content in wheat cultivars. SNP application also increased the activities of NR and antioxidant enzymes, including GSHPx, GR, and GST in wheat cultivars exposed to B toxicity. All of the tested LMWOAs including succinic, propionic, butyric, oxalic, formic, malic, malonic, and benzoic acids were increased by SNP treatment in the shoots and roots of both wheat cultivars exposed to B toxicity. In conclusion, results obtained from this study have demonstrated that interactive effects of SNP with B considerably reduced the toxic effects of B in wheat cultivars.